Bioassay for total serum bioactivity of Atractylodes lancea - Kesara Na-Bangchang; Anurak Cheoymang; Nadda Muhamad; Inthuon Kulma (Wolters Kluwer Medknow Publications, 2023)
The study aimed to establish a bioassay for total bioactivity of Atractylodes lancea (AL) in human serum samples. Inhibition of bacterial growth (Staphylococcus aureus ATCC 25923) was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The calibration curve (0, 0.39, 0.78, 1.56, 3.13, 2.56, and 50 ng/ml) was linear with correlation coefficients >0.990. The limit of quantification (LOQ) was 1.66 mg/ml using 20-ml serum sample. The developed bioassay method meets the standard of the bioanalytical method for determination of serum bioactivity of AL.